Middle Ear Adenoma: Case Report and Discussion - D. Isenring; T. F. Pezier; B. Vrugt; A. M. Huber (Case Reports in Otolaryngology)
Introduction. Despite modern radiological workup, surgeons can still be surprised by intraoperative findings or by the pathologist’s report. Materials & Methods. We describe the case of a 52-year-old male who was referred to our clinic with a single sided conductive hearing loss. He ultimately underwent middle ear exploration and excision of a middle ear tumour followed by second look and ossiculoplasty a year later. Results. Though preoperative CT and MRI scanning were suggestive of a congenital cholesteatoma, the pathologist’s report diagnosed a middle ear adenoma. Discussion. Middle ear glandular tumors are extremely rare and, despite numerous histological techniques, continue to defy satisfactory classification. Most surgeons advocate surgical excision though evidence of the tumour’s natural course and risk of recurrence is lacking.